2021
DOI: 10.1001/jamanetworkopen.2021.9452
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prostate-Specific Antigen Velocity With Clinical Progression Among African American and Non-Hispanic White Men Treated for Low-Risk Prostate Cancer With Active Surveillance

Abstract: IMPORTANCEThe association of prostate-specific antigen velocity (PSAV) with clinical progression in patients with localized prostate cancer managed with active surveillance remains unclear and, to our knowledge, has not been studied in African American patients.OBJECTIVES To test the hypothesis that PSAV is associated with clinical progression in patients with low-risk prostate cancer treated with active surveillance and to identify differences between African American and non-Hispanic White patients. DESIGN, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…Hence, those subjects deserve particular attention during TRT. The PSA velocity, previously considered a marker for TRT withdrawn and prostate biopsy, has been criticized [174,175]. Accordingly, the European Association of Urology guidelines suggest that PSA density (PSAD) with a Prostate Imaging Reporting and Data System (PI-RADS) score (≥ 3) might help in decision for further evaluations [173].…”
Section: Remarksmentioning
confidence: 99%
“…Hence, those subjects deserve particular attention during TRT. The PSA velocity, previously considered a marker for TRT withdrawn and prostate biopsy, has been criticized [174,175]. Accordingly, the European Association of Urology guidelines suggest that PSA density (PSAD) with a Prostate Imaging Reporting and Data System (PI-RADS) score (≥ 3) might help in decision for further evaluations [173].…”
Section: Remarksmentioning
confidence: 99%
“…The 1,400 Black men in this study experienced increased risk of upgrading (but not metastasis) at lower PSA velocities than their White counterparts. 34…”
Section: Psa-based Biomarkersmentioning
confidence: 99%
“…The 1,400 Black men in this study experienced increased risk of upgrading (but not metastasis) at lower PSA velocities than their White counterparts. 34 PSA density is a measure that normalizes PSA levels to prostate volume, eliminating the variability introduced by prostate size. There is abundant evidence PSA density is associated with increased risk of upgrading and reclassification while on AS, 8,11 and that it outperforms base PSA in predicting these events.…”
Section: Psa-based Biomarkersmentioning
confidence: 99%
“…Policy and guideline recommendations regarding diagnostic and therapeutic interventions are driven by the availability and quality of trial data, and the lack of available evidence hinders developing recommendation for the early detection of prostate cancer in Black men around the world, though NCCN has attempted to do so for sub-Saharan Africa [90]. PSA and PSA derivatives (i.e., PSA density) may vary by race/ethnicity [91,92]. Studies have demonstrated Black men undergoing prostate cancer screening have higher PSA levels [93] and more rapid increases in PSA [94] compared with men of other race/ethnicities, which could be due to biological, social or lifestyle factors, or access to care.…”
Section: A Multi-institutional Radical Prostatectomy Cohort Of Patien...mentioning
confidence: 99%